2010
DOI: 10.1371/journal.pone.0012255
|View full text |Cite
|
Sign up to set email alerts
|

Sounds Move a Static Visual Object

Abstract: BackgroundVision provides the most salient information with regard to stimulus motion, but audition can also provide important cues that affect visual motion perception. Here, we show that sounds containing no motion or positional cues can induce illusory visual motion perception for static visual objects.Methodology/Principal FindingsTwo circles placed side by side were presented in alternation producing apparent motion perception and each onset was accompanied by a tone burst of a specific and unique frequen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
28
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(33 citation statements)
references
References 19 publications
5
28
0
Order By: Relevance
“…In our opinion, this initial pair of mechanisms should be statistical co-occurrence and shared properties (particularly connotations) since these two mechanisms are best supported by the available empirical evidence. There is compelling evidence that statistical co-occurrences can create crossmodal correspondences between dimensions (e.g., Baier, Kleinschmidt, & Müller, 2006;Ernst, 2007;Teramoto, Hidaka, & Sugita, 2010;Zangenehpour & Zatorre, 2010), though this still remains to be demonstrated for sound symbolic associations. There is also evidence of similar connotations creating crossmodal correspondences (e.g., L. P.…”
Section: Outstanding Issues and Future Directionsmentioning
confidence: 99%
“…In our opinion, this initial pair of mechanisms should be statistical co-occurrence and shared properties (particularly connotations) since these two mechanisms are best supported by the available empirical evidence. There is compelling evidence that statistical co-occurrences can create crossmodal correspondences between dimensions (e.g., Baier, Kleinschmidt, & Müller, 2006;Ernst, 2007;Teramoto, Hidaka, & Sugita, 2010;Zangenehpour & Zatorre, 2010), though this still remains to be demonstrated for sound symbolic associations. There is also evidence of similar connotations creating crossmodal correspondences (e.g., L. P.…”
Section: Outstanding Issues and Future Directionsmentioning
confidence: 99%
“…What is more, repeated exposure to the statistical co-occurrence of particular pairs of stimuli can also influence the coupling prior, even for pairs of stimulus dimensions that happen, initially, to be unrelated (e.g., Ernst, 2007; see also Teramoto, Hidaka, & Sugita, 2010). So, for example, Ernst (2007) demonstrated that exposing people to an arbitrary correspondence between the luminance of a visual object and its felt stiffness, a haptically ascertained stimulus property that is not correlated with luminance in the natural environment, can give rise to a change in the coupling prior.…”
mentioning
confidence: 99%
“…Interestingly, SCVM was specifically observed for the previously exposed visual field [3] and eye [6]. These behavioral findings suggest that the associations are formed relatively early visual processing.…”
Section: Introductionmentioning
confidence: 64%
“…Previous behavioral studies have demonstrated several characteristics of SCVM. Teramoto et al [3] tested 20 and 5…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation